FAILURE ANALYSIS ON SLINGER DISK PIPE OF PURIFIED TEREPHTALIC ACID (PTA) VESSEL - Sukandar, Sukandar; Triwibowo, Triwibowo; Heryana, Yana (Majalah Ilmiah Pengkajian Industri, 2020)
Slinger disk pipe is a rotary part of PTA vessel with function as anti-fog by swinging hot water to the shell wall to remove solid PTA at the shell wall. Failure took place on this slinger disk pipe. The purpose of failure analysis is to find the root cause of failure. Methods conducted in this failure analysis are examination and testing of fractography, metallography, chemical composition, hardness, and calculation of bending stress. Examination on the fracture surface by fractographic method revealed fatigue fracture with the presence of multiple beachmarks. The position of those multiple beachmarks gave indication of alternation rotation of slinger disk pipe. Examination by metallographic method revealed that initial cracks initiated from heat affected zone of pipe and strengthening plates weld joint. However, result of chemical composition examination and hardness test showed that material of slinger disk pipe were in accordance with lean duplex 2205. Calculation of bending stress gave supporting data of various load effects to slinger disk pipe. Therefore, failure of the slinger disk pipe was caused by fatigue fracture which were initiated from head affected zone of pipe and strengthening plates weld joint.